Pathogenic free-living amoebic encephalitis from 48 cases in China: A systematic review - Chen, Xiang-Ting; Zhang, Qian; Wen, Si-Yuan; Chen, Fei-Fei; Zhou, Chang-Qing (Frontiers in Neurology, 2023)
Background Free-living amoebae (FLA) including Naegleria fowleri, Acanthamoeba spp., and Balamuthia mandrillaris can become pathogenic and cause severe cerebral infections, named primary amoebic meningoencephalitis (PAM), granulomatous amoebic encephalitis (GAE), and balamuthia amoebic encephalitis (BAE), respectively. FLA encephalitis has been reported across China, but the clinical data descriptions and analytical results of these different reports vary widely. Currently, no consensus treatment has been established. We conduct a systematic review to evaluate the exposure location, clinical symptoms, diagnosis, treatment, and prognosis of three FLA encephalitis and aim to reveal the differences between three FLA encephalitis in China. Methods We used MEDLINE (PubMed interface), EMBASE, China National Knowledge Infrastructure (CNKI), Wanfang database, and China Biology Medicine disc (CBMdisc) databases for literatures published and manually retrieve the hospital records of our hospital. The search time was up to August 30, 2022, with no language restrictions. Results After excluding possible duplicate cases, a total of 48 patients of three FLA encephalitis were collected. One from the medical records of our hospital and 47 patients from 31 different studies. There were 11 patients of PAM, 10 patients of GAE, and 27 patients of BAE. The onset of PAM is mostly acute or subacute, and the clinical symptoms are acute and fulminant hemorrhagic meningoencephalitis. Most patients with GAE and BAE have an insidious onset and a chronic course. A total of 21 BAE patients (77.8%) had skin lesions before onset of symptoms. Additionally, 37 cases (77.1%) were diagnosed with FLA encephalitis before death. And there were 4 of PAM, 2 of GAE, and 10 of BAE diagnosed using next generation sequencing. No single agent can be proposed as the ideal therapy by itself. Only 6 cases were successfully treated. Conclusions This review provides an overview of the available data and studies of FLA encephalitis in China and identify some potential differences. FLA encephalitis is a rare but pathogenic infection, and physicians should early identify this encephalitis to improve survival.